Double-well atom trap for fluorescence detection at the Heisenberg limit - Stroescu, Ion; Hume, David B.; Oberthaler, Markus K. (Physical review. A, Atomic, molecular, and optical physics, 2015)
We experimentally demonstrate an atom number detector capable of simultaneous detection of two mesoscopic ensembles with single-atom resolution. Such a sensitivity is a prerequisite for quantum metrology at a precision approaching the Heisenberg limit. Our system is based on fluorescence detection of atoms in a hybrid trap in which a dipole barrier divides a magneto-optical trap into two separated wells. We introduce a noise model describing the various sources contributing to the measurement error and report a limit of up to 500 atoms for single-atom resolution in the atom number difference.